2010
DOI: 10.1074/jbc.m110.136630
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Detergent-insoluble Tau Is Involved in Neuronal Loss but Not in Synaptic Loss

Abstract: Neurofibrillary tangles (NFTs), which consist of highly phosphorylated tau, are hallmarks of neurodegenerative diseases including Alzheimer disease (AD). In neurodegenerative diseases, neuronal dysfunction due to neuronal loss and synaptic loss accompanies NFT formation, suggesting that a process associated with NFT formation may be involved in neuronal dysfunction. To clarify the relationship between the tau aggregation process and synapse and neuronal loss, we compared two lines of mice expressing human tau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 33 publications
2
101
1
1
Order By: Relevance
“…Sarkosylinsoluble fractions from tissue protein extracts were prepared as previously described (Kimura et al, 2010). Briefly, frozen hippocampi of P301L tau mice were homogenized in Tris-buffered saline (10 mM Tris, 150 mM NaCl, pH 7.4) containing protease inhibitors (1 mg/ml antipain, 5 mg/ml pepstatin, 5 mg/ml leupeptin, 2 mg/ml aprotinin, and 0.5 mM 4-[2-aminoethyl]benzenesulfonyl fluoride hydrochloride) and phosphatase inhibitors (1 mM NaF, 0.4 mM Na 3 VO 4 , and 0.5 mM okadaic acid).…”
Section: Methodsmentioning
confidence: 99%
“…Sarkosylinsoluble fractions from tissue protein extracts were prepared as previously described (Kimura et al, 2010). Briefly, frozen hippocampi of P301L tau mice were homogenized in Tris-buffered saline (10 mM Tris, 150 mM NaCl, pH 7.4) containing protease inhibitors (1 mg/ml antipain, 5 mg/ml pepstatin, 5 mg/ml leupeptin, 2 mg/ml aprotinin, and 0.5 mM 4-[2-aminoethyl]benzenesulfonyl fluoride hydrochloride) and phosphatase inhibitors (1 mM NaF, 0.4 mM Na 3 VO 4 , and 0.5 mM okadaic acid).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the toxic nature of ROS, we would expect that some neurons were also damaged in the brain as a result of the alloxan injection. Meanwhile, our previous report suggested that the substantial neuronal losses observed in P301L TG mice are the consequence of insoluble tau accumulation (Kimura et al, 2010). Therefore, it is difficult to extrapolate how the alloxan-induced decrease in insoluble tau levels might influence neuronal numbers.…”
Section: Discussionmentioning
confidence: 95%
“…To test the impact of oxidative stress on the phenotypes associated with tau misfolding and dysfunction in vivo, we injected alloxan into TG mice that express human mutant (P301L) tau (Kimura et al, 2010). A single intraperitoneal injection of alloxan at 100 mg kg )1 of body weight, on average, failed to significantly change either blood glucose concentration or body weight ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations